Trajectory of human migration: insights from autosomal and non-autosomal variant clustering patterns - Samayeta Sarkar Tuli; Joyatry Sarker; Mrinmoy Saha Roddur; Anik Biswas; Reefa Nawar; Tahmina Akter; Md. Wahid Murad; Abu Ashfaqur Sajib (Journal of Advanced Biotechnology and Experimental Therapeutics)
Genetic variations present in the Y chromosomal and mitochondrial DNA provide the mole-cular basis to support the archeological and anthropological evidence that formulates the theories for describing the trajectory of human migration, which started almost 200,000 years ago out of Africa. These genetic variations have long been used as ancestry informative markers (AIMs) in forensics and evolutionary studies, primarily because of their uniparental inheritance and lack of recombination, despite the fact that gender-specific gene flow and socio-cultural practices may cause discrepancies. Moreover, the genetic markers on the Y chromosome constitute only a minor fraction of the entire human genome. Here, we analyzed over 75 million genetic variants (single nucleotide variants (SNVs) and short insertion-deletion (InDels)) within consecutive 2500000 base pair windows in the autosomal as well as non-autosomal chromosomes of 22 populations in four major geographic regions that are cataloged in the 1000 Genomes Project to understand the clustering patterns of the autosomal and non-autosomal variants. While autosomal and X-chromosomal variants cluster the populations of similar geographic regions together, Y-chromosomal variants constantly place the East Asian Japanese and the European Finnish populations in a single clade in hierarchical clusters. This comprehensive genome-wide analysis essentially introduces new insights into mapping the path of human migration based on the Y-chromosomal and other chromosomal variants. [ J Adv Biotechnol Exp Ther 2025; 8(1.000): 139-149]